A case of bacteriemic mediastinitis due to Prevotella buccae after cardiac surgery. (February 2020) - Duployez, C.; Loiez, C.; Hund, R.; Jegou, B.; Decoene, C.; Wallet, F.
Abstract: Mediastinitis is a well-known complication of open-heart surgery. Strictly anaerobic bacteria are rarely found in this condition, unlike in descending mediastinitis. We report the case of a mediastinitis due to Prevotella buccae after surgical replacement of the aortic valve and triple coronary artery bypass in an immunocompetent 76 year-old man. The bacteria were found in pure culture on blood samples and surgical samples. This case emphasizes the need to perform anaerobic cultures in case of sternal wound infection after open-heart surgery. Highlights: Post-operative mediastinitis is a classic complication of open-heart surgery. Implication of anaerobic bacteria in postcardiac surgery mediastinitis is uncommon. This is the 1st description of monomicrobial P.buccae poststernotomy mediastinitis. In post-cardiac surgery medistinitis, anaerobic etiology should be considered.